AN ANALYSIS OF POWER EXERCISE IN H. G. WELLS' THE WAR OF THE WORLDS - Mustaffa, Rifki Zamzam (2017)
The novel entitled The War of the Worlds has several issues which is interesting to be studied. One of them is the issue of power which becomes the main focus of the present study. Since the novel portrays the war between humans and aliens (specifically, the Martians' invasion of the Earthlings) and arguments among humans (the Earthlings) illustrate the exercise of power, the bases of power proposed by Raven (2008) are applied in this study to examine the power-related phenomena. Furthermore, this study is also expected to give insights in investigating and understanding the way power can manifest itself in literary works. The exercise of power is analyzed by focusing on conflicts among characters, particularly the conflicts between the Martians and the Earthlings as well as the conflicts among the Earthlings. The findings of the study discovered that the distinctive ways of exercising power, particularly in the conflicts, are through coercion and information. This shows that the exercise of power in the novel is comprehended to be the way text shows its bias towards logical and empirical way of thinking. ; ---- Sebuah novel yang berjudul The War of the Worlds memiliki banyak isu yang dapat diteliti lebih mendalam, diantaranya adalah isu power. Isu power ini kemudian diteliti secara spesifik dengan menerapkan teori bases of power yang dikemukakan oleh Raven (2008). Alasan teori bases of power diterapkan dalam penelitian ini dikarenakan adanya penggambaran perang antara manusia dan alien (khususnya invasi Martians terhadap Earthlings) serta argumen diantara penduduk bumi itu sendiri (Earthlings) yang memicu munculnya permainan power. Penelitian ini juga bertujuan untuk memberikan beberapa ide baru dalam meneliti isu-isu yang berkaitan dengan power, khususnya mengenai beragam cara power dapat dimainkan dan dimunculkan didalam karya sastra tertentu. Selanjutnya, permainan power ini dianalisis dengan melihat konflik-konflik antarkarakter yang terjadi dalam novel, khususnya konflik yang melibatkan Martians dan Earthlings serta konflik-konflik yang terjadi diantara Earthlings. Hasil penelitian menyatakan bahwa cara-cara khusus dalam memainkan power, terutama power yang muncul dalam konflik, adalah power yang berdasarkan coercion dan information. Hal ini menunjukkan bahwa permainan power yang muncul dalam novel bertujuan untuk menunjukkan keberpihakan teks terhadap pemikiran-pemikiran yang berdasarkan pada logika dan kejadian-kejadian yang bersifat empiris.